Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this and **thousands** of other questions.

See more answers at brainly.com

lol another multiple choice?

Yes
A. (x+2)^2/25 - (y-1)^2 = 1
B. (x-1)^2 - (x+2)^2/25 = 1
C. (x+2)^2/25 - (x-1)^2 = 1

ok well that makes it much easier

actually there must be something wrong here, because the \(y^2\) term comes first

\[y^2 - 25x^2 + 4y + 50x - 46 = 0
\]

these are my only options :/

if the last one is really \[\frac{(y+2)^2}{25}-(x-1)^2=1\] then go with that one

thank you, i'm going to go with it.